Atividade vocal, ocupação e densidade populacional de duas corujas em fragmentos florestais do extremo Norte da Mata Atlântica - Gomes, Carlos Salústio (2024)
Understanding the activity and distribution patterns of animals about environmental factors is crucial for species conservation. In the Atlantic Forest domain, 72% of owl species show population declines, making it essential to conserve both species and habitats. The use of passive acoustic monitoring offers opportunities to collect data on the vocal activity and habitat use of little-studied species, contributing to long-term monitoring and effective conservation. This work seeks to fill gaps in understanding the vocal activity and habitat use patterns of owls that occur in the far north of the Atlantic Forest, specifically in the north of the Pernambuco Endemism Center, Brazil. Our objectives were: (1) to investigate the vocal activity patterns of two nocturnal owls, the Tropical Screech-Owl (Megascops choliba) and the Spectacled Owl (Pulsatrix perspicillata), to contribute to monitoring protocols for the conservation of both species; and (2) to identify the environmental factors that affect the occupancy of P. perspicillata, estimate its population density, and map the hotspots of occupancy and density of the species to aid locate priority conservation areas. In the first part of the study, we found that M. choliba vocalized more frequently at 7 PM, 1 AM, and 4 AM, with the highest vocal activity occurring approximately 4 hours before sunrise and 10 min after sunrise. P. perspicillata vocalized more frequently between 8 PM and 10 PM, and at 2 AM, with the highest vocal activity occurring about 3 hours after sunset and 4 hours before sunrise. The vocal activity rate of P. perspicillata was best explained by the moonlight index, tree density, and the detection of M. choliba, while the vocal activity rate of M. choliba was best explained by air temperature and understory density. In the second part, we identified that P. perspicillata responds to environmental variations both at the patch scale and at the 1000-ha landscape scale, and its occupancy is positively affected by the presence of primary forests and areas with greater topographic roughness. The regions of high occupancy and density are concentrated in protected areas, indigenous lands, and other patches with high potential for conservation. The results of this study may aid in identifying favorable scenarios for the efficient monitoring of forest night owls and establishing protocols for the conservation of species that are sensitive to the effects of forest loss and that lack information related to habitat use.